2020
DOI: 10.4103/jfmpc.jfmpc_1077_19
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance: Call for rational antibiotics practice in India

Abstract: It is a well-known fact that microorganisms are developing resistance to antimicrobial drugs present in the market that is known as antimicrobial resistance (AMR). This resistance in microbes is a great matter of concern among the scientific fraternity. This review article focuses on antibiotics and their respective resistant microbes, factors that cause resistance among microbes, and consequences of AMR at global as well as Indian scenario. This article would be a helpful resource in nutshell for making the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Similarly, the present study also revealed higher use of quinolones and third-generation cephalosporins, both in terms of frequency and quantity of use. The high use of quinolones in India could have paved the increased resistance toward fluoroquinolones and cephalosporins among Gram-negative and Gram-positive bacteria in the country ( 52 ). Such AMU data at the regional level helps to identify the trends in antimicrobial usage and serves to inform health policy makers to initiate evidence-based responses to tackle this public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the present study also revealed higher use of quinolones and third-generation cephalosporins, both in terms of frequency and quantity of use. The high use of quinolones in India could have paved the increased resistance toward fluoroquinolones and cephalosporins among Gram-negative and Gram-positive bacteria in the country ( 52 ). Such AMU data at the regional level helps to identify the trends in antimicrobial usage and serves to inform health policy makers to initiate evidence-based responses to tackle this public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Chandra et al emphasize the issue of AMR in India and the requirement for judicious antibiotic usage in the nation. 34 They underline the growing issue of AMR in India and the requirement for an efficient strategy that can slow down the emergence and spread of bacterial drug resistance. This further emphasizes the necessity for education and awareness campaigns aimed at educating the general public and healthcare professionals about the risks of antibiotic overuse and the significance of taking antibiotics cautiously.…”
Section: Antibiotic Resistance Genes Found In the Microbiotamentioning
confidence: 99%
“…This further emphasizes the necessity for education and awareness campaigns aimed at educating the general public and healthcare professionals about the risks of antibiotic overuse and the significance of taking antibiotics cautiously. 34 However, the focus of Brinkac et al 53 is on how AMR affects the human microbiome. The human microbiome has been defined by the authors as a complex population of bacteria that is significant for human health in several ways.…”
Section: Antibiotic Resistance Genes Found In the Microbiotamentioning
confidence: 99%
See 1 more Smart Citation